Causal Relationship Between Housing Policies implemented since late 1990s and Real Estate Bubble in China - Faltus, Jakub (2025)
This thesis examines the causal relationship between housing policies implemented since the late 1990s and the formation of a real estate bubble in China. Through a mixed approach combining trend development and regression analyses, the research investigates how fiscal and urban/land policies have influenced real estate prices and market dynamics. The thesis aims to verify whether fiscal and urban/land policies correlate with price fluctuations while controlling for other statistically significant factors, such as GDP growth. The study also checks for policy contradictions and unintended consequences contributing to market instability. The research sheds light on complex interactions between policy interventions and broader economic forces contributing to China's real estate bubble.